The Restoration of the Church of the Epiphany in Chelmuzhi in 1913 by D.V. Mileev to the Celebration of 300 Anniversary of the Romanov Dynasty - Meliukh, Ekaterina A. (Actual Problems of Theory and History of Art, 2014)
This article is focused on the Epiphany Church in Chelmuzhi. The main aim of this article is to consider the preparatory and restoration work processes on the example of one of the oldest monuments of wooden architecture in the region of Zaonezhye. The article discusses the design features of the church, a brief history of pogost, investigates the connection of the church to the Romanov family and celebration of the 300th-year anniversary from the moment of accession of Mikhail Romanov, and the restoration work under the guidance of Dmitry V. Mileev. It was discovered that the researcher avoided dismantling the Church in the course of the repair, and even removed the late alterations. Detailed reporting and recording enabled other architects to monitor all his works. In addition, reviewing the archival sources helped to uncover the whole complicated bureaucratic process accompanying the restoration works in the early 20th century — from the petitions of the local clergy to resolutions of the Imperial Archaeological Commission.
Keywords: Dmitry V. Mileev; architecture; wooden architecture; restoration; 20th century; Chelmuzhi; the 300th anniversary of the Romanov dynasty; the Imperial Archaeological Commission